The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1051/0004-6361/201116958
|View full text |Cite
|
Sign up to set email alerts
|

Multi-colour optical variability of the blazar 3C 454.3 in 2007–2010

Abstract: Context. We present our optical multiband (B and R) observations of the blazar 3C 454.3, which were acquired over 30 nights from August 2007 to December 2010. Aims. We analyse our data to study the optical emission variability properties of 3C 454.3. Methods. The observations were carried out using both the 1 m EOS Telescope (EST) and the 0.8 m Tsinghua-NAOC Telescope (TNT) simultaneously in most nights at the Xinglong Observatory of National Astronomical Observatories, Chinese Academy of Sciences (NAOC). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Our observations did not detect any noticeable time lags between the intra-night variations in the B and R bands, so that the individual measurements do not indicate a loop path. Similar results were reported by Zhai et al (2011) for the blazar 3C 454.3. However, the loop paths described by the nightly means may suggest that BL Lac has a spectral hysteresis in its inter-night variations (Wu et al 2007).…”
Section: Colour Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…Our observations did not detect any noticeable time lags between the intra-night variations in the B and R bands, so that the individual measurements do not indicate a loop path. Similar results were reported by Zhai et al (2011) for the blazar 3C 454.3. However, the loop paths described by the nightly means may suggest that BL Lac has a spectral hysteresis in its inter-night variations (Wu et al 2007).…”
Section: Colour Analysissupporting
confidence: 91%
“…The results indicated that no measurable time delay longer than the exposure interval between B and R bands during the four nights. This coincidence of the B and R band variations suggests that the radiation in both wavebands may be similar in active states and arise from the same region in the jet (Zhai et al 2011). …”
Section: Correlated Variabilitymentioning
confidence: 73%
See 2 more Smart Citations
“…In this paper, we concentrate on the multicolour intra-night variability of CTA 102 during its 2012 and 2016 maxima. So far, several objects have been multicolour (quasi)-simultaneously monitored on intranight time scales, among which S4 0954+65 (Papadakis et al 2004;Bachev et al 2016), 3C 454.3 (Bachev et al 2011Zhai et al 2011), BL Lacertae (Zhai & Wei 2012), S5 0716+714 (Stalin et al 2009;Wu et al 2012), etc. To the best of our knowledge, this is the first such study for CTA 102.…”
Section: [Pks 0736+017]; Bachev 2015 [S4 0954+65] Etc)mentioning
confidence: 99%